Engaging with the claim of Roma people through twitter: who is behind the hashtags? - Aiello-Cabrera, Emilia; Troya, Maria; Flecha, Ainhoa; Khalfaoui, Andrea (Frontiers in Sociology, 2023)
Grassroots Roma communities play a pivotal role in organizing at the grassroots level, advocating for their rights, and challenging anti-Roma sentiment across Europe. Nevertheless, there remains a need for a deeper understanding of how these efforts manifest within the digital landscape. Within the overarching framework of the Narratives4Change project (EU Marie Curie Action, Nr. 841,355), this study seeks to examine the use of Twitter as a platform for advocating Roma-related issues. Specifically, it investigates the types of actors engaged in tweeting about Roma-related content and explores potential variations in profiles (organizations vs. individuals) based on the content being tweeted. The analysis encompasses six Roma-related hashtags spanning the years 2017 to 2020: #RomaLivesMatter, #InternationalRomaDay, #OpreRoma, #OpreRomnia, #MujerGitana, and #RomaWomen. The findings reveal that organizations are most active when employing the hashtags #InternationalRomaDay and #MujerGitana, whereas for the other hashtags studied, individual users dominate. Our data underscore the untapped potential of social media spaces and their ecosystems as strategic tools for advocacy and mobilization in support of Roma rights throughout Europe.